Meconium periorchitis: An incidentally diagnosed rare entity during inguinal herniorraphy - Gül Durmuş; Özlem Boybeyi-Türer; Mina Gharibzadeh-Hizal; Saniye Ekinci; Nural Kiper (The Turkish Journal of Pediatrics)
Meconium periorchitis (MPO) is a rare disorder caused by meconium peritonitis with the leakage of meconium into the scrotal sac through the patent processus vaginalis. MPO may be rarely detected during inguinal hernia repair. The association of MPO with cystic fibrosis is rarely seen. We present a male infant with the complaint of left groin swelling, compatible with reducible inguinal hernia. An herniotomy was carried out and the greenish nodules with calcifications were detected. Histopathological examination was compatible with MPO. Two months later the patient was diagnosed with atypical cystic fibrosis. Clinicians should be aware of MPO presentations and its appearance on the hernia sac to prevent unnecessary orchiectomy.